2018
DOI: 10.12681/jhvms.15466
|View full text |Cite
|
Sign up to set email alerts
|

IgY extraction and purification from chicken egg yolk

Abstract: ABSTRACT.The interest for immunoglobulin Y (IgY) isolation arises from the possible applications of these immunoglobulins in diagnostics and therapeutics. Powered whole eggs or yolks have been used in veterinary medicine as an inexpensive immunoglobulin Y source for the treatment of enteric diseases. Incorporating feed grade egg yolk antibodies into animal diets has been examined extensively in an attempt to limit pathogenic diarrhea causing by Escherichia coli in swine, and limit Salmonella establishment in c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 29 publications
1
12
0
Order By: Relevance
“…Since then, the number of articles, books or chapters published on the production of IgY in chicken has increased. At the same time, the number of articles on methods of extraction and purifying IgY from eggs expanded ( Nilsson et al., 2012 ; Bizanov, 2017 ). The number of articles, patents and companies working on diagnostic products also increased ( Lee et al., 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Since then, the number of articles, books or chapters published on the production of IgY in chicken has increased. At the same time, the number of articles on methods of extraction and purifying IgY from eggs expanded ( Nilsson et al., 2012 ; Bizanov, 2017 ). The number of articles, patents and companies working on diagnostic products also increased ( Lee et al., 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…The latest studies confirmed the influence of IgY as an active antibacterial agent for Gram-positive bacteria; however, no killing influence had been recorded for Gram-negative bacteria ( 12 ). Cytokine activity was highly stimulated by purified IgY compared to other food supplements ( 41 ). Moreover, in our study, broiler meat from the group supplemented with IgY showed the most desirable meat quality characteristics, color, shearing force, and water holding capacity ( 12 ).…”
Section: Discussionmentioning
confidence: 99%
“…Campylobacter-specific IgY titers in egg yolks were determined before and after lyophilization, as previously described by Hermans et al, (2014) with minor changes to the protocol. Egg yolks were diluted 1/5 (vol/vol) in HBSS, mixed thoroughly, and incubated overnight at 4 C. Lyophilized egg yolks were first diluted 1/2 (wt/ vol) in HBSS because half of the egg yolk consists of water (Bizanov, 2017). The supernatant, containing the water-soluble fraction of the egg yolk, was collected for IgY quantification using ELISA.…”
Section: Determination Of Egg Yolk Igy Titersmentioning
confidence: 99%
“…Oral administration of antibodies is a promising strategy for controlling enteric bacterial and viral infections in humans and animals, such as Salmonella enterica, Escherichia coli, Campylobacter jejuni, Clostridium perfringens, rotaviruses, and coronavirus (Mine and Kovacs-Nolan, 2002;Schade et al, 2005;Chalghoumi et al, 2009a;Yegani and Korver, 2010;Gadde et al, 2015;Hedegaard and Heegaard, 2016). A cost-efficient method to produce such antibodies is through hyperimmunization of chickens and collecting the egg yolks, containing high amounts of antibodies (Bizanov, 2017).…”
Section: Introductionmentioning
confidence: 99%